Anti‐TNF‐α therapy for patients with sepsis: a systematic meta‐analysis. Issue 4 (18th February 2014) - Lv, S.; Han, M.; Yi, R.; Kwon, S.; Dai, C.; Wang, R.
Summary Objective In humans, the role of anti‐tumour necrosis factor (TNF)‐α therapy in severe sepsis and septic shock is debatable. The aim of this meta‐analysis was to determine the efficacy of anti‐TNF‐α therapies against placebo in patients with severe sepsis or septic shock. Methods A structured literature search was undertaken to identify randomised controlled trials (RCTs) conducted in patients with severe sepsis or septic shock receiving anti‐TNF‐α therapy or placebo. A meta‐analysis on relative risk (OR) with a 95% confidence interval (95% CI) was performed. Results Seventeen studies with a total of 8971 patients were included. When all forms of anti‐TNF‐α therapy were pooled together, there was a significant reduction of 28‐day all‐cause mortality with respect to placebo (OR = 0.91, 95% CI: 0.83–0.99; p = 0.04). Subgroup analysis showed that anti‐TNF‐α antibodies (monoclonal and polyclonal) reduced mortality (OR = 0.90, 95% CI: 0.81–0.99; p = 0.04). Monoclonal antibodies enhanced survival (OR = 0.91, 95% CI: 0.82–1.00; p = 0.05), while polyclonal antibodies or receptor blockers did not enhance survival (OR = 0.71, 95% CI: 0.39–1.28, p = 0.25; OR = 0.95, 95% CI: 0.78–1.17, p = 0.65). There was a trend towards better survival in patients with high levels of IL‐6 (> 1000 pg/ml) and patients with shock if they were treated with anti‐TNF‐α therapy (OR = 0.85, 95% CI: 0.72–1.00; OR = 0.80, 95% CI: 0.62–1.04). Publication bias and statistical heterogeneity (I2 < 50% and p > 0.1) were absent. Sensitivity analysis suggests that these results are highly stable. Conclusions This meta‐analysis suggests that in patients with severe sepsis (before shock), immunotherapy with anti‐TNF‐α monoclonal antibodies reduces overall mortality. In patients with shock or high levels of IL‐6 (> 1000 pg/ml), anti‐TNF‐α therapy may improve survival.